1995
DOI: 10.1016/0014-5793(94)01360-d
|View full text |Cite
|
Sign up to set email alerts
|

Selective inhibition of cytosine‐DNA methylases by polyamines

Abstract: We have advanced the hypothesis that polyamines affect DNA methylation and thus promote the expression of developmentally controlled genes. We demonstrate that the activity of cytosine-DNA methyltransferases HpaII, HhaI, HaeIII and SssI is inhibited by physiological concentrations of polyamines.On the other hand, activity of the adenine-DNA methyltransferase EcoRI, and restriction enzymes HpaII, HhaI, HaeIII and EcoRI, is insensitive to polyamine concentrations up to 40 mM.Our results indicate that the effect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

1996
1996
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 28 publications
0
17
0
Order By: Relevance
“…However, according to Heby et al (1988) and Ruiz-Herrera (1994), methylation alterations could also be associated with changes in the specific relations between the different individual free polyamines (Table 1). High levels of Spd+Spm and low levels of Put related to reproductive ability in radiata pine, as reported in hazelnut (Rey et al 1994), could imply low dSAM contents (Heby 1995;Ruiz-Herrera et al 1995). This is a substrate of Spd synthase, and also a competitive inhibitor of the DNA methyltransferase, which could increase its action, thereby emphasising the degree of DNA methylation, and possibly cause gene silencing (Razin and Riggs 1980).…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…However, according to Heby et al (1988) and Ruiz-Herrera (1994), methylation alterations could also be associated with changes in the specific relations between the different individual free polyamines (Table 1). High levels of Spd+Spm and low levels of Put related to reproductive ability in radiata pine, as reported in hazelnut (Rey et al 1994), could imply low dSAM contents (Heby 1995;Ruiz-Herrera et al 1995). This is a substrate of Spd synthase, and also a competitive inhibitor of the DNA methyltransferase, which could increase its action, thereby emphasising the degree of DNA methylation, and possibly cause gene silencing (Razin and Riggs 1980).…”
Section: Resultsmentioning
confidence: 91%
“…Owing to the greater ability of long-chain polyamines, compared with Put, to bind to the genomic DNA (Panagiotidis et al 1995;Pelta et al 1996), the increase in these polyamines causes conformational changes in DNA, exposing certain areas to methylation enzymes (Tabor and Tabor 1984;Smith 1985). Furthermore, a decrease in the Put/(Spd+Spm) ratio coincides with low levels of decarboxylated S-adenosylmethionine (dSAM) (Ruiz-Herrera 1994;Heby 1995;Ruiz-Herrera et al 1995;Heby et al 1988) which is a competitive inhibitor of the DNA methyltransferase. This consequently provokes an increase in the degree of methylation of the genomic DNA.…”
Section: Introductionmentioning
confidence: 96%
“…Impairment of movement or of the dissociation of chromatin-associating proteins from chromosomal DNA due to lacking polyamines could impede transcription, recombination and repair, and lead to chromosomal instability and an increased rate of mutation. Specific interactions of polyamines with DNA that imply chromatin configuration are also suggested by the observation that DNA methyltransferases are inhibited by polyamines [112]. However, the fact that Chinese hamster ovary (CHO) cells exposed to DFMO had no significant effect on the condensation state of chromatin during the cell cycle [113] is a caveat against generalisations concerning polyamine pool size changes and functional changes of chromatin.…”
Section: Binding To Anionic Structuresmentioning
confidence: 99%
“…Additionally, some researchers also suggested that polyamines have ability to protect replicating DNA from oxidative damages (Khan et al, 1992;Miyamoto et al, 1993;D'Agustino et al, 2005). It was first reported that polyamines had the role of selective inhibition cytosine-DNA methylases by prevent both the binding and activity of these enzymes (Ruiz-Herrera et al, 1995). Although we have a lot of knowledge about the effects of picloram on non-target organisms, there is no report shown the effect of picloram on DNA methylation and DNA damage (by using the RAPD technique).…”
Section: Introductionmentioning
confidence: 98%
“…Especially, polyamines such as putrescine, spermidine, spermine may establish a correlation with proteins, nucleic acids, membrane phospholipids and cell wall constitutents. Numerous studies claim that polyamines bound to guard DNA from enzymatic degradation, mechanical shearing and X-ray irradiation and also stabilize RNA to counteract of ribosomal dispersion (Miyamoto et al, 1993;Ruiz-Herrera et al, 1995). Additionally, some researchers also suggested that polyamines have ability to protect replicating DNA from oxidative damages (Khan et al, 1992;Miyamoto et al, 1993;D'Agustino et al, 2005).…”
Section: Introductionmentioning
confidence: 99%